Building Trust in Data Linkage: A Framework for Quality Assurance and Governance - Efrosini Setakis; Giulia Mantovani; Liliana Valles Carrera; Mia Noonan (International Journal of Population Data Science, 2025)
Objectives Data linkage is crucial for research, healthcare, and policymaking, yet it is often treated as a purely technical process rather than a modelling challenge. This abstract introduces a Quality Assurance Framework for Data Linkage to ensure appropriate governance, transparency, and methodological rigor while balancing privacy, ethics, and public trust.